2008
DOI: 10.1128/cvi.00050-08
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Evidence for Functional Rather than Structural Mimicry by aShigella flexneriY Polysaccharide-Mimetic Peptide

Abstract: Shigellosis, caused by Shigella species (gram negative), is a prominent, and the most infectious, diarrheal disease. Shigella flexneri, the species responsible for the highest mortality rate, is endemic in most developing countries (23). The 13 serotypes of S. flexneri, with the exception of serotype 6, result from structural modifications of the O-antigen polysaccharide (PS), the outer portion of the lipopolysaccharide (LPS) on the bacterial surface, which is both an essential virulence factor and a protectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…23 In order to test these hypotheses, we synthesized protein conjugates of the octapeptide 24 and recently evaluated their immunogenicities. 16 Indeed, we found that, although the kinetics of the immune response in mice were slow, cross-reactivity was observed, and an effective prime-boost strategy was developed. 16 We now report the design of two chimeric glycopeptides ( Fig.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…23 In order to test these hypotheses, we synthesized protein conjugates of the octapeptide 24 and recently evaluated their immunogenicities. 16 Indeed, we found that, although the kinetics of the immune response in mice were slow, cross-reactivity was observed, and an effective prime-boost strategy was developed. 16 We now report the design of two chimeric glycopeptides ( Fig.…”
Section: Introductionmentioning
confidence: 98%
“…[14][15][16][17] In addition to their ability to elicit carbohydrate-binding antibody responses, these peptide mimics should focus the immune responses on particular epitopes since greater discrimination of the peptides for the corresponding antibody-combining sites has been observed, 18 thus minimizing autoimmune reactions with self structures where the original carbohydrate antigens would pose a threat as immunogens. [17][18][19] Shigella flexneri Y is a virulent bacterium that causes bacillary dysentery by invading the colonic mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that despite the differences in peptide versus oligosaccharide binding, a protein conjugate of the peptide ligand is immunogenic and elicits an immune response that is cross-reactive with the bacterial polysaccharide. [6] Thus, the peptide is an antigenic mimic of the polysaccharide.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Traditionally, carbohydrate-based vaccines are weakly immunogenic, as determined by the thymus dependent immune response; therefore, studies were undertaken to identify carbohydrate-mimetic peptides as surrogate ligands. [4,5] Using phase display, a weakly immunogenic [6] carbohydrate-mimetic peptide of the Shigella flexneri Y O-linked polysaccharide, with the amino acid sequence MDWNMHAA 1 (Figure 2), was identified to be cross-reacAbstract: Saturation transfer difference (STD)-NMR spectroscopy was used to probe experimentally the bioactive solution conformation of the carbohydrate mimic MDWNMHAA 1 of the O-polysaccharide of Shigella flexneri Y when bound to its complementary antibody, mAb SYA/J6. Molecular dynamics simulations using the ZymeCAD Molecular Dynamics platform were also undertaken to give a more accurate picture of the conformational flexibility and the possibilities for bound ligand conformations.…”
Section: Introductionmentioning
confidence: 99%
“…29 In support of this, others have found synthetic MD10 peptide conjugated to other carrier proteins to be very poorly immunogenic. 30 Moreover, while recombinant peptides displayed on pVIII can be resolved by NMR, 31 it is likely the SPDP amide and disulfide linkages introduce a degree of conformational flexibility to a conjugated peptide. The 4E10 L peptide, on the other hand, is extremely hydrophobic, and in recombinant form may embed itself in hydrophobic "grooves" between pVIII monomers, 32 making it poorly immunogenic as a recombinant fusion.…”
Section: The Immune Response To Filamentous Phagementioning
confidence: 99%